Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.14740/jocmr3816
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia in Patients With Hereditary Hemochromatosis: Real or Myth?

Abstract: Background Hereditary hemochromatosis (HH) is an autosomal recessive disorder affecting iron metabolism, resulting in iron accumulation in tissue parenchymal cells. Missense mutations result in homozygosity or heterozygosity for substitutions in the HFE gene, with the most common being C282Y and H63D. Methods With an aim to evaluate an association between polycythemia and HH, retrospective chart review was performed for 152 patients with known HFE mutations. Parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Beutler et al report only a slightly increased mean hemoglobin level in patients with hereditary hemochromatosis screened in the ambulatory setting [10]. Asif et al observed a median hemoglobin level of 15.5 mg/dL in their homozygous C282Y population, which is closely reflective of the hemoglobin values reported by our study [11]. Another study by Barton et al reports that only patients with C282Y homozygosity (and not other genotypic variants) have higher mean hemoglobin values when compared to healthy matched controls; the mean hemoglobin levels of their untreated homozygous C282Y probands was reported to be 15.0 mg/dL (±1.3), which also closely matches that reported in our study [6].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Beutler et al report only a slightly increased mean hemoglobin level in patients with hereditary hemochromatosis screened in the ambulatory setting [10]. Asif et al observed a median hemoglobin level of 15.5 mg/dL in their homozygous C282Y population, which is closely reflective of the hemoglobin values reported by our study [11]. Another study by Barton et al reports that only patients with C282Y homozygosity (and not other genotypic variants) have higher mean hemoglobin values when compared to healthy matched controls; the mean hemoglobin levels of their untreated homozygous C282Y probands was reported to be 15.0 mg/dL (±1.3), which also closely matches that reported in our study [6].…”
Section: Discussionsupporting
confidence: 83%
“…Polycythemia has been previously explored in various studies in the context of hereditary hemochromatosis [6,11]. Polycythemia in this setting is thought to be a consequence of elevated transferrin saturation levels, resulting in increased iron uptake by erythroid precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Furthermore, previous studies have demonstrated that individuals with heterozygosity for H63D gene will have normal to slightly elevated biochemical indices of iron overload compared with wild-type individuals 18,19 or may tend to have higher baseline hemoglobin levels when compared with persons with C282Y or compound C282Y/H63D heterozygosity. 20 In addition, it was previously shown that high-volume transfusion donors (super donors) who had the H63D heterozygosity were characterized by significant reduction in hepcidin production compared with the wildtype super donors. 21 On the contrary, both testosterone and SGLT-2i in in vivo and clinical studies have been shown to suppress hepcidin and increase erythropoietin levels thus promoting environment stimulating hematopoiesis and erythrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several research groups found HFE variants at higher frequencies among patients with unexplained erythrocytosis, i.e., idiopathic erythrocytosis (IE), compared with the general population (Biagetti et al, 2018;Burlet et al, 2019;Gurnari et al, 2019). Similarly, patients with the HFE variants had significantly higher Hb and Ht values than normal (Barton et al, 2000;Asif et al, 2019). It was suggested that HFE mutations could induce erythropoiesis through higher iron bioavailability, since iron is dedicated to the synthesis of Hb (Hentze et al, 2010;Biagetti et al, 2018;Burlet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%